Retorika Visual dan Dramatisasi Karakter Mimi Peri dalam Sosial Media sebagai Komoditas - Yurisma, Dhika Yuan; Erdiana, Setya Putri; Fahminnansih, Fenty (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
The use of sensationalism as a medium to boost popularity is not a new phenomenon in the entertainment industry, as demonstrated by Mimi Peri, one of the Instagram celebrities on social media. She leverages her gained popularity as a source of livelihood, presenting herself as a flirty woman with masculine features and adding dramatic content based on her imagination as an angel from heaven. By using Burke's visual rhetoric theory, which is divided into three elements: pathos, logos, and ethos, we can examine the meaning of signs and the purpose of the visuals displayed on Mimi Peri's Instagram account. Additionally, dramatism theory is used as supporting theory to further analyze Mimi Peri's character in greater depth. Mimi Peri has received both tremendous appreciation and criticism from netizens, but the backlash she receives only increases her popularity. The more people criticize her, the more she is discussed. This indicates that Mimi Peri intentionally portrays herself as a dramatic figure to achieve popularity and become a commodity in social media.